Features of Composite Additives Production Technology - Sobirovna , Mavlanova Firangiz (Miasto Przyszłości, 2024)
The article analyzesmodern diesel fuels and requirements for them. Particular attention is paid to additives that improve the low-temperature characteristics of diesel fuels. The role of multifunctional composite additives has been studied. The mechanism of action of additives in diesel fuels has been studied. The features of the production technology of composite additives are revealed.